EFEKTIVITAS MODEL HYBRID LEARNING DALAM MENINGKATKAN KUALITAS PEMBELAJARAN - Gerawati, Adela Putri; Wardani, Kusuma; Yusuf, Putri Sinta Nuriah; Elmenes, Fika Ardyani; Rustam, Najla; Khairunnisa, Arin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The development of information and communication technology has encouraged innovation in education, including the emergence of hybrid learning models that combine online and offline learning. This study aims to examine the effectiveness of hybrid learning model in improving learning quality through literature review method. The study was conducted by reviewing scientific articles from national journals over the past ten years, obtained through a search on Google Scholar. The results show that hybrid learning has a positive impact in improving learning motivation, learning outcomes, and critical thinking skills of students. This model also supports independent learning, flexibility of time and place, and active involvement of learners. The implementation of hybrid learning is in line with several learning theories such as Constructivism Theory, Social Learning Theory, and Connectivism Theory. However, the effectiveness of this model implementation is highly influenced by the readiness of technological infrastructure, digital competencies of teachers and students, and policy support from educational institutions. The findings are expected to be a reference for educators and policy makers in designing responsive and sustainable learning strategies in the digital era.